Planning for regional sustainability in uncertain times: urbanisation through the waves of global crises - Abdul Hadi Harman Shah; Abdul Samad Hadi; Shaharudin Idrus; Ahmad Fariz Mohamed (Universiti Kebangsaan Malaysia, 2011)
Planning for sustainability in uncertain times, especially due to global crises, often proceeds tentative, requiring the placing aside of grander comprehensive plans for a more achievable short term gains. While boom periods characterised by the influx of large capital seems to be constantly increasing rapidly, and bust periods show uncontrolled decline in general,a more detailed look will show more fluctuations and uncertainties; with decisions to expand a business or fold taking longer and that there are more decisions involved than what may seem at the surface. This paper presents the findings of a study on urbanisation in the Bernam Linggi region, an area that spans the states of Perak, Selangor and Negeri Sembilan in Malaysia. It is fast becoming an urban conurbation with different centres currently fusing together to create a contiguous development area. The paper presents how these changes impact upon and are impacted by the infrastructure and the community, resulting in changing livability and sustainability potential. The paper argues that planning such a region requires an analysis that does not assume stability and employs a complexity approach to understand the planning needs for the development of the Bernam-Linggi region to capture the intricate processes of regional growth.